ChemInform Abstract: A Chemoselective Oxidation of Monosubstituted Ethylene Glycol: Facile Synthesis of Optically Active α‐Hydroxy Acids. Issue 48 (2nd December 2014) - Chinthapally, Kiran; Baskaran, Sundarababu
Abstract Under optimized conditions, chemoselective and racemization‐free oxidation of enantiopure monosubstituted ethylene glycols such as (I) and (IV) is achieved in good yields using the TEMPO‐NaOCl reagent system.